REPOSITIONING TEACHERS FOR THE ACTUALIZATION OF THE MILLENNIUM DEVELOPMENT GOALS (MDGs) - Sarkinfada, Halima (Sokoto Educational Review, 2020)
The actualizations of the millennium Development Goals are met to improve the society. The teacher as an executor and dispenser of Education should be regarded as the societal target for growth and development. This paper has highlighted how the teacher should be repositioned in the society by facilitating the teacher instructional delivery and design Information communication Technology (ICT) with adequate remuneration. The teacher when adequately repositioned will play a vital role in actualizing certain goals e.g. Eradication of extreme poverty and hunger, achieving universal basic education, promotes gender equality and empowers women and combat HIV/AIDS and other diseases. It is in the view of this paper that the repositioned teacher will be flexible in theories, strategies and practice that may be applied to several categories of teaching and learning situations.